The adult offending outcomes of adolescents who have perpetrated a sex offense: is sexual offending in adolescence indicative of things to come? - Chouinard-Thivierge, Stéphanie (Youth violence and juvenile justice, 2023)
Being adjudicated for a sex offense carries significant social, legal, and penal implications that are almost unparalleled and adolescents are no exception to this differential treatment by the justice system. This highlights the relevance of providing criminal career information concerning future offending among adolescents who have a record for a sex offense as they age and become adults. Based on prospective longitudinal data collected from a sample of male adolescents enrolled in the Pathways to Desistance study (n = 1170), negative binomial regression models are conducted to investigate the relationship between having a juvenile record for a sex offense and the frequency of general offending in early adulthood (i.e., 18 years old and over). Results show that adolescents who have perpetrated a sex offense have significantly lower levels of involvement in offending during early adulthood, whether based on official or self-reported data. Findings are discussed in terms of policy and theoretical implications.